2019
DOI: 10.3390/ani9100707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Defined Course Doses (DCDvet) for Blanket and Selective Antimicrobial Dry Cow Therapy on Conventional and Organic Farms

Abstract: Simple SummaryThe general public is increasingly concerned about using antibiotics to treat animals in food production systems. It is vital that sick animals should be treated and that veterinarians should have treatment options available to prevent unnecessary suffering. Nevertheless, farmers and veterinarians are working together to reduce antibiotic use. In Austria, antibiotics can only be obtained from veterinarians and any antimicrobials dispensed must be reported to the authorities. This study aimed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The study revealed that cows receiving antimicrobial DCT [109] had a significantly higher cure rate (86.6%) than the cows that did not receive antimicrobial treatment (59.2%) at this time [110]. In DCT, the antibiotics prevent new infections as well as treat the existing infections.…”
Section: Selective Dry Cow Therapy (Dct)mentioning
confidence: 99%
“…The study revealed that cows receiving antimicrobial DCT [109] had a significantly higher cure rate (86.6%) than the cows that did not receive antimicrobial treatment (59.2%) at this time [110]. In DCT, the antibiotics prevent new infections as well as treat the existing infections.…”
Section: Selective Dry Cow Therapy (Dct)mentioning
confidence: 99%
“…However, as dry cow therapy is an important part of the antimicrobial use statistics of dairy farms, a comparison of the corrected DCDvet/cow/year was carried out between those farms testing positive for the presence of ESBL-producing E. coli and those testing negative. The DCD/cow/year value was corrected by the replacement rate and calving interval for each of the farms included here, as described elsewhere [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…"Blanket" or conventional DCT is the treatment of all quarters of all cows with an antibiotic at drying-off is a common practice in most dairy farms. Whereas in selective DCT infected cows are treated with antibiotics along with teat sealant and uninfected cows are treated with teat sealant only (Firth et al, 2019). Given the concerns about antibiotic resistance, this is a challenge for the farmers to consider if it is necessary to treat all cows in their herds.…”
Section: Selective Dry Cow Therapymentioning
confidence: 99%